Quid pro quo: The impact of explicit brand mentions and reciprocity in brand alliance communications - Roosens, Bram; Dens, Nathalie; Lievens, Annouk (European journal of marketing, 2019)
PurposeThis paper aims to assess the effects of explicit partner brand mentions (as opposed to a mere partnership mention) in communications by brand allies on consumers’ purchase intention and willingness to pay for an innovation, as mediated by the perceived relational embeddedness of the allies and their respective perceived corporate credibility. In Study 1, the authors investigate the effects of (reciprocal) explicit brand mentions by both allies (as opposed to by a single ally) and further test whether explicit brand mentions moderate spillover effects from the ally. In Study 2, the authors investigate the effect of reciprocity of explicit brand mentions and whether this is moderated by a company’s experience.Design/methodology/approachThe authors conduct two online experiments. Study 1 (N = 216) is a four-level between-subjects experiment (single communication by Partner A with explicit brand mention, single communication by Partner B with explicit brand mention, explicit brand mentions by both allies and mere partnership mention by both allies) where participants judge a social alliance related to a new tablet. Study 2 (N = 376) builds upon these findings in a 4 (explicit brand mentions by both allies; mere partnership mention by both allies; explicit brand mention by Partner A, mere partnership mention by Partner B; explicit brand mention by partner B, mere partnership mention by Partner A) × 2 (Partner A experience: established vs startup) between-subjects experimental design for a co-created battery.FindingsSpillover effects from one ally to the other are stronger with explicit brand mentions than with a mere partnership mention. There is no added value of two allies communicating over one, provided that both partners explicitly mention their partner brand. However, when allies do communicate separately, it is crucial that an explicit brand mention is reciprocated. This effect is explained by an increase in the perceived relational embeddedness of the partners, which in turn positively influences their corporate credibility. This effect does not differ depending on a company’s experience.Originality/valueThis research is one of the first to study effects of how a brand alliance is communicated and extends previous studies on the effects of communication about brand and co-creation alliances by demonstrating that communications moderate spillover effects, that brand mention reciprocity is crucial, and by introducing the concept of perceived relational embeddedness.